Characterizing Earthquake Source Parameters and b Value Variations in Subduction and Fault Segments: Implications for Seismic Hazard Analysis - Abdi Jihad; Vrieslend Haris Banyunegoro; muksin umar; marwan ramli; Syamsidik Syamsidik; yunita idris; Andi Azhar Rusdin (Directorate for Research and Community Services (LPPM) ITB, 2024)
Earthquake sources in Aceh have distinct characteristics. Understanding the seismic characteristics of each earthquake source is crucial for comprehending earthquake cycles and assessing seismic hazards. A key parameter in characterizing an earthquake source is the b-value, which indicates the relationship between the number of earthquakes and their magnitudes, influenced by the magnitude of completeness (Mc). The present study analyzed the seismic characteristics of two subduction zone segments and sixteen fault segments using the least squares method on selected earthquake data specific to each segment. The analysis revealed that the b-value ranged from 0.5 to 0.6 in the subduction zone segments and from 0.3 to 1.0 in the fault segments. These variances in b‑value reflect the different seismic characteristics of the earthquake sources that shape the tectonic settings in Aceh. A lower b-value signifies an elastic zone capable of holding higher stress levels, whereas a higher b-value indicates a brittle zone that can only withstand lower stress levels.